2012
DOI: 10.1007/s10801-012-0367-z
|View full text |Cite
|
Sign up to set email alerts
|

The stable set of associated prime ideals of a polymatroidal ideal

Abstract: The associated prime ideals of powers of polymatroidal ideals are studied, including the stable set of associated prime ideals of this class of ideals. It is shown that polymatroidal ideals have the persistence property and for transversal polymatroids and polymatroidal ideals of Veronese type the index of stability and the stable set of associated ideals is determined explicitly.1991 Mathematics Subject Classification. 13C13, 13A30, 13F99, 05E40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(110 citation statements)
references
References 21 publications
2
108
0
Order By: Relevance
“…Then In order to conclude our proof that I must satisfy one of the conditions (a),(b) or (c), it remains to be shown that if there exists l ∈ [r], such that p l is principal, then I satisfies one of the conditions (a) or (c). If m ∈ Ass(S/I), then G I is connected and I is fully supported by [8,Theorem 4.3]. Otherwise, we show that p i is principal for all i ∈ [r].…”
Section: Polymatroidal Ideals With Stable Projective Dimensionmentioning
confidence: 83%
See 1 more Smart Citation
“…Then In order to conclude our proof that I must satisfy one of the conditions (a),(b) or (c), it remains to be shown that if there exists l ∈ [r], such that p l is principal, then I satisfies one of the conditions (a) or (c). If m ∈ Ass(S/I), then G I is connected and I is fully supported by [8,Theorem 4.3]. Otherwise, we show that p i is principal for all i ∈ [r].…”
Section: Polymatroidal Ideals With Stable Projective Dimensionmentioning
confidence: 83%
“…, p r . As in [8] we define the graph G I associated with I as follows: the vertex set of G I is [r] and {i, j} is an edge of G I if and only if G(p i ) ∩ G(p j ) = ∅.…”
Section: Polymatroidal Ideals With Stable Projective Dimensionmentioning
confidence: 99%
“…We know from [15,Corollary 3.5] that equality occurs in the above inequality, if I is a polymatroidal ideal. In fact, we will see in the next section that equality holds in Burch's inequality for a larger class of ideals, namely, the class of normal ideals.…”
Section: 2mentioning
confidence: 99%
“…. , x r ] over the field K. As introduced in [9] we define the index of depth stability of I to be the number dstab(I) := min{n 0 1 | depth S/I n = depth S/I n 0 for all n n 0 }.…”
Section: Preliminarymentioning
confidence: 99%